2011
DOI: 10.1002/prca.201000136
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of molecular pathways, biomarkers and drug targets for diabetic nephropathy

Abstract: Only the combined molecular feature landscapes closely reflect the clinical implications of DN in the context of hypertension and diabetes. Omics data integration on the level of interaction networks furthermore provides a platform for identification of pathway-specific biomarkers and therapy options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Migration of immune cells into the renal is a feature of early DN, and it is implicated in the development of this complication [3437]. Previous studies also have found C1S and C1R to be differentially expressed in DN [38, 39]. In our study, C1S and C1R were regulated by LEF1 and hsa-miR-33a.…”
Section: Discussionsupporting
confidence: 67%
“…Migration of immune cells into the renal is a feature of early DN, and it is implicated in the development of this complication [3437]. Previous studies also have found C1S and C1R to be differentially expressed in DN [38, 39]. In our study, C1S and C1R were regulated by LEF1 and hsa-miR-33a.…”
Section: Discussionsupporting
confidence: 67%
“…This approach also allowed the association of biomarker candidates with relevant pathophysiologic pathways in diabetic nephropathy (for example, oxidative stress responses, extracellular matrix-receptor interactions or chemokine signalling). 131 Similarly, an analysis of indepth proteomic data from a mouse model of folic acidinduced AKI involved the assessment of 6,564 nonredundant proteins from kidney. 132 The investigators verified the upregulation of several proteins previously associated with AKI, and identi fied novel biomarker candidates suggesting the involvement of the glutamatergic signalling system in AKI.…”
Section: Systems Medicine Approachesmentioning
confidence: 99%
“…In a pilot study, six metabolites suggested by consortium members as strong candidate CKD biomarkers were analysed. This resulted in the finding of shared descriptors between the genes for each metabolite, thus ranking the relevance of the metabolites for the kidney disease [29]. This capacity is now being augmented by a weighting algorithm to prioritise the metabolite-related gene sets.…”
Section: Omics Integrationmentioning
confidence: 99%
“…A literature mining of papers of 17 omics studies related to CKD[29] assisted in benchmarking the GeneKid pipeline (Figure 2). Additional benchmarking was performed based on a list of 26 initial biomarkers (22 proteins, two peptides, one autoantibody and one nucleotide), prioritised by the extent of relevant gene annotations, using the GeneCards database for obtaining diseases, compounds and pathway relationships.…”
Section: Omics Integrationmentioning
confidence: 99%